Syzygiella teres (Machantiophyta) in the Elephant Island, Antarctica - Suarez, Guillermo Martin (2019)
Background and aims: The known liverworts flora of Elephant Island, Antarctica, is composed by six species: Cephalozia badia, Cephaloziella varians, Anthelia juratzkana, Barbilophozia hatcheri, Lophoziopsis excisa, and Syzygiella jacquinotii. The aim of this communication is to record Syzygiella teres in the island. M & M: The liverworts were studied by conventional technics for bryophytes and mounted in Hoyer's solution. Results: Syzygiella teres is characterized by unlobed leaves with colorless marginal border. The species is briefly described and illustrated. A comparative key for all liverworts known from Elephant Island is presented.